Indoor feeding or grazing - Rinne, Kalle; Suvitie, Marjatta; Rinne, Sirkka-Liisa (Wageningen Pres, 1994)
Indoor feeding and grazing with dairy cows were compared at two levels of energy and protein from concentrates during three growing seasons. Grazed cows produced more milk and the milk contained more protein than that of completely indoor fed cows. The number of animals culled due to mastitis was higher for completely indoor fed cows than for grazed cows. No difference was found in the fertility of the cows.